Multigenic and Induced Systemic Resistance in Plants - Sadik, Tuzun; Elizabeth, Bent (Springer US : Imprint: Springer, 2006)
This comprehensive volume consists of a series of up-to-date reviews, each incorporating current models and knowledge related to mechanisms of resistance either expressed constitutively or induced systemically in plants. Each chapter covers a topic related to the phenomenon of plant resistance to fungal and bacterial pathogens, insects, nematodes, viruses or abiotic stress in plants, as well as the application of this knowledge to protect crops now and in the future. Researchers, upper-level undergraduate and graduate students, and those teaching courses in plant physiology, entomology and plant pathology will find this volume a much needed asset. Featured Topics include: QTL analysis of multigenic disease resistance in plant breeding Ultrastructural studies in plant disease resistance Chemical signals in plant resistance: salicylic acid Signaling in plant resistance responses: divergence and cross-talk of defense pathways Tree defenses against insects Chemical signals in plants: jasmonates and the role of insect-derived elicitors in responses to herbivores Engineering plants for durable disease resistance Commercialization of plant systemic defense activation: theory, problems and successes.